Planning for Climate Change in the NSW Local Aboriginal Land Council Estate - Heidi Norman; Therese Apolonio; Evelyn Yong; Calise Liu; Sharanjit Paddam (Cosmopolitan Civil Societies: An Interdisciplinary Journal)
The Aboriginal land estate in NSW is uniquely vulnerable to the physical risks of climate change and this jeopardises the rights and interests of First Nations peoples. This paper presents the findings of research and knowledge exchange between a cross-disciplinary research team and Local Aboriginal Land Councils (LALCs). The research team, with expertise on Aboriginal land rights, energy policy and actuarial modelling, assessed physical risk to LALC lands in regional NSW. At workshops held in the NSW Far Western Zone and in northern and southern NSW, LALCs truth-tested these findings. By sharing their knowledge and priorities for living on their land during climate change, these LALCs highlighted the limitations and cultural bias of Western models of assessing risk. This paper explains the context of the Aboriginal land estate and climate change risks and shares our preliminary findings, along with some considerations for supporting LALCs to develop strategies for climate adaptation and mitigation.